Elastic Power Bands Affect the Improvement of PencakSilat Athlete Sickle Kicks - Irsan Kahar; Najamuddin Najamuddin; Ahmad Ahmad; Andi Heri Riswanto; Rasyidah Jalil (JUARA : Jurnal Olahraga, 2023)
This study aims to determine the effect of Elastic Power Bands training on increasing the sickle kick in the Pencak Silat Athletes of Porprov Kab. Luwu. This research method is quantitative research in the form of an experimental One-Group Pre-test Post-test Design carried out by giving X treatment to the subject. The population in this study was the PencakSilat Athletes of the Province of Luwu Regency, totaling 19 people. The sampling technique was used when all population members were sampled, namely the saturated sample technique. The data collection technique used a sickle kick ability test through pair training. The results of this study indicate that the Elastic Power Bands exercise positively affects the ability to perform crescent kicks in the Porprov Pencak Silat Athletes of Luwu Regency. The test results of the athlete's sickle kick using the Elastic Power Bands exercise, in the pre-test, the average value obtained was 66.4667, and in the post-test, the average value obtained was 80.2667. From the two tests performed, it can be seen that the average post-test has a higher score than the average pre-test, which means that the Elastic Power Bandster exercise has an effect on increasing crescent kick ability. So there is an average difference between the results of the pre-test and post-test, which means that there is a significant effect of Elastic Power Bands training on the pencaksilat sickle kick.